(untitled) (International journal of artificial intelligence, 2026)
This article examines the role of toponyms in folk tales as a reflection of national linguocultural worldviews. Toponyms function not only as geographical markers but also as carriers of cultural memory, historical experience, and ethnic identity. Through the analysis of folk narratives, the study reveals how place names encode symbolic meanings, collective values, and culturally specific concepts. The research emphasizes that toponyms in folklore contribute to shaping the cognitive and axiological space of a nation, reflecting its worldview, traditions, and perception of reality.